Dialética Da Libertação: Não Violência, Protesto E Arte Em Herbert Marcuse - Magalhaes, Rogerio Silva De [UNIFESP] (2018)
Aside The 1969 An Essay On Liberation, Marcuse Writes A Series Of Essays And Lectures In The 1960s In Which He Criticizes The Violence Of The Status Quo Against Protests That Are Taking The Streets In Several Countries Of The Advanced Industrial Society As Well As The Violence Of The Vietnam Invading Troops. However, These Texts Also Reveal Marcuse"S Point Of View About The Moviments Of Protest, Mainly, The Student One. In Texts Like The 1965 Essay "Repressive Tolerance", The 1967 Lecture "The Problem Of Violence And The Radical Opposition", The 1968 Article "Reflections On The French Revolution" And The 1969 Article "Student Protest Is Nonviolent Next To The Society Itself", Among Others, Marcuse Develops A Reflection On The Forms Of Protest Of The New Left. In Light Of The Diagnosis Of The Working Class Integration To The Apparatus Of Production And Consumption In The Advanced Industrial Society, The Movements Of The New Left Like The Student One Are Considered Catalysts To The Radical Change Of Society. On